Effect of Bacterial and Yeast Starters on the Formation of Volatile and Organic Acid Compounds in Coffee Beans and Selection of Flavors Markers Precursors During Wet Fermentation - Martinez, Silvia Juliana; Bressani, Ana Paula Pereira; Dias, Disney Ribeiro; Simão, João Batista Pavesi; Schwan, Rosane Freitas (Frontiers in Microbiology, 2019)
Coffee quality has recently become a high demand of coffee consumers, due to all the specialty coffees available on the market. Specialty coffees can be generated by favoring growth of some groups of microorganisms during fermentation or by using starters. Just as yeast, a variety of bacteria can be used to generate important flavor precursors. The aim of this work was to test the efficiency of coffee sterilization and adhesion of microbial cells on beans, to evaluate the effect of yeast and bacterial starters on the production of organic and volatile compounds, and selection of potential flavor marker precursors during the wet fermentation. Three yeast and six bacterial starters were inoculated in coffee beans. Coffee sterilization and microbial adhesion was observed by scanning electron microscopy (SEM). Organic compounds were detected by high performance liquid chromatography (HPLC) and volatile compounds by gas chromatography–mass spectrometry (GC–MS). Micrographs from the SEM showed that sterilization was efficient, because there were no microbial cells after autoclaving for 5 min. Also, it was observed an increase of microbial cells from 0 to 48 h of fermentation. Malic, lactic, and acetic acid were only detected in the bacterial treatments. Volatile compounds: 4-ethenyl-1,2-dimethoxybenzene, heptadecanol, 4-hydroxy-2-methylacetophenone, and 1-butanol,2-methyl were only found in yeast treatments. Guaiacol was only produced by the inoculated B. subtilis starters. In conclusion, yeast starters were better producers of volatile alcohols and bacterial starters of acid compounds. This study allowed the selection of potential flavor marker precursors, such as heptadecanol, 4-hydroxy-2-methylacetophenone, 7-methyl-4-octanol, and guaiacol.